Effect of drip irrigation scheduling on yield and quality of Nagpur mandarin (Citrus reticulata Blanco) fruits - P.S. Shirgure (Indian Journal of Horticulture, 2023)
A experiment was conducted on 7-9 year-old bearing Nagpur mandarin (Citrus reticulata Blanco) based on evaporation replenishment (ER) irrigation scheduling to identify the irrigation water requirement through drip irrigation system during 2009-2012 at different stages. The fruit and quality was found significantly influenced under various evaporation replenishment (ER) based drip irrigation scheduling treatments. The highest fruit yield (21.48 tonnes/ha) was observed under irrigation at 80% ER in stages I-V and 30% ER in stage VI. Among the fruit quality irrigation scheduled at 80% ER in stages I-V and 30% ER in stage VI produced higher TSS, juice content and lower acidity. The highest TSS: acid ratio (12.7) was found in the irrigation scheduled with 30% ER in stage VI and 80% ER in stages I-V followed by the drip irrigation scheduled with 80% ER in all I-VI stages (12.2).